(untitled) (Salam International Academic Journal, 2019)
The traffic police around the world check vehicle papers and plate numbers to confirm if the vehicles are registered with the government. Nowadays this process takes place manually, and there are numerous hindrances associated with it. For instance, may be a vehicle has fake papers or fake plate number. Or May be a vehicle hasn’t paid its taxes. So the traffic police are unable to identify or trace each vehicle correctly due to fake papers that look like genuine papers. Hence a system must be designed in which the mentioned issues need to be addressed. The sole intent of this paper is to design a cloud based system that verifies each vehicle’s plate number through a single SMS. Traffic police should only send a plate number of an intended vehicle to the cloud using GSM technology; the system should send all the necessary information back to the concerned authority for confirmation. This paper consists of three main modules, the IT infrastructure module, the private cloud module and the GSM SMS module. This system is very easy to use, fast and can prevent many crimes too.